2020
DOI: 10.29244/agrokreatif.6.2.150-158
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Usaha Minyak Kelapa Tradisional untuk Meningkatkan Pendapatan IKM Desa Posso, Kabupaten Gorontalo Utara

Abstract: Posso is one of the villages which is located in Kwandang sub-district, North Gorontalo, Province of Gorontalo. It has the potential of coconut plantations with a production capacity of around15,000 coconuts/month. In order to increase the potential of village, the government formed a jointly successful SMEs that are produces traditional coconut oil. The purpose of this activity is to develop a traditional coconut oil business to increase SMEs incomes. The method applied are technology transfer, provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
1
1
2
Order By: Relevance
“…This promotional activity done by placing some products on merchants around the Tukah Yeh Unda or building a small shop specialized in selling the traditional coconut oil to extend the marketing area. This finding was contrary to Azis et al (2020) that emphasizing online marketing through online platforms such as Facebook and Tokopedia to promote the product.…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…This promotional activity done by placing some products on merchants around the Tukah Yeh Unda or building a small shop specialized in selling the traditional coconut oil to extend the marketing area. This finding was contrary to Azis et al (2020) that emphasizing online marketing through online platforms such as Facebook and Tokopedia to promote the product.…”
contrasting
confidence: 78%
“…They also found that there was a limited number of economic derivative products produced from the oil. Azis et al (2020) in their study found that unappealing packaging and no laboratory test conducted to list the chemical composition of the traditional coconut oil produced by the local business as the problem encountered in running the business.…”
Section: Introductionmentioning
confidence: 99%
“…Pemberian informasi produk dapat menambah kepercayaan konsumen dalam memilih suatu produk. (Azis et al, 2020), menjelaskan semakin menarik kemasan yang digunakan maka berpeluang dalam meningkatkan nilai penjualan karena konsumen akan menjadi lebih tertarik dan infrmasi nilai gizi yang diberikan juga menjadi acuan konsumen untuk membeli.…”
Section: Pendahuluanunclassified
“…Bungkil kopra adalah komoditi yang paling tinggi ekspornya dilihat dari segi volume dan jumlahnya. Jumlah produksi kelapa terbesar di Provinsi Gorontalo terdapat di daerah Kabupaten Gorontalo (Azis, 2020).…”
Section: Pendahuluanunclassified